International legally binding treaty on business and human rights - weighing the pros and cons - Majuri, Satu-Pauliina (fi=Turun yliopisto|en=University of Turku|, 2017)
Economic actors, such as transnational corporations, have become powerful actors within the world’s economy and they are increasingly using their economic power to influence the actions of states. Although international law is directly applicable to states, and most states sign up to international human rights conventions, international human rights law, as it currently stands, does not impose direct human rights obligations on corporations. This thesis examines why a binding instrument on business and human rights is, or is not desirable. I portray the elements that might challenge the necessity of such a treaty and explore to whom and under what conditions a treaty should play role. I research the pros and cons and take critically into account the problems associated with the treaty and its purpose, which is the better implementation of the UN Guiding Principles. The goal of this thesis is to understand and explain objectively the ongoing debate around the Treaty. Proponents of the treaty claim that there is inadequacy of existing international legal framework on business and human rights. However, this study has shown that there are several tools already taking place. The United Nations human rights monitoring mechanisms have issued guidance, the Office of the UN high Commissioner for Human Rights has provided further assistance and the Council of Europe has given its recommendations. Furthermore, ILO has its big role to play in the field of protecting human rights against businesses, not forgetting instruments created by OECD and ISO. This gives reason to further research how to use these tools, even if non-binding, more efficiently. Despite the rift between the two sides, a business and human rights treaty seems achievable. When achieving the consensus it would be crucial that existing human rights treaty provisions and human rights standards that are already taking place are synergetic with a new treaty.